Treatment of Pediatric Burkitt Lymphoma in Turkey - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
This study aimed to assess the demographic data and treatment results of children who were diagnosed with Burkitt lymphoma and treated according to the Berlin-Frankfurt-Munster-95 (BFM) protocol in a single institution. A total of 48 patients (37 boys, 77%) with a median age of 8 years (range 2 to 16 years) at diagnosis, were evaluated. Primary tumor sites were abdomen (70.8%), head and neck (22.9%), peripheral lymph node (2%), bone (2%), and testis (2%). The 5-year overall survival (OS) and event-free survival (EFS) were 78.1 +/- 4% and 76.6 +/- 6%, respectively. In univariate analysis, hemoglobin level less than 10 g/dL, cerebrospinal fluid (CSF) positivity and dialysis requirement at diagnosis were found to be important reverse predictor factors for EFS (P; 0.001, 0.001, 0.004, respectively). In multivariate analysis, hemoglobin level less than 10 g/dL and dialysis at diagnosis were found to be important reverse predictor factors for EFS (P; 0.0001). The EFS of our patients was lower than the values achieved with BFM-95 protocol in other centers. This study provides evidence that low hemoglobin level, CSF positivity and dialysis at diagnosis were important predictor factors for EFS in children with Burkitt lymphoma.
Keywords: Burkitt's lymphoma; childhood; prognostic values; NON-HODGKIN-LYMPHOMA; FRANKFURT-MUNSTER GROUP; ACUTE-LYMPHOBLASTIC-LEUKEMIA; TUMOR LYSIS SYNDROME; LARGE-CELL LYMPHOMA; NHL-BFM 90; CLINICAL CHARACTERISTICS; CHILDREN; CHILDHOOD; ADOLESCENTS